Pemberdayaan Masyarakat Berbasis Komunitas Zakat Pada Masa Pandemi Di Desa Kahayya, Kabupaten Bulukumba - Ainul Fatha Isman (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2021)
Zakat as one of the institutions in Islam, has a spiritual dimension and covers many aspects of community empowerment that include various aspects such as economic, social, health, education and religion, especially in the event of a pandemic. One of the community empowerment programs by zakat institutions is Zakat Community Development. One of the community empowerments programs by zakat institutions in this research to find out and analyze the concept of empowerment in the form of Zakat Community Development during the pandemic in Kahayya Village, Bulukumba Regency. The method in this study is qualitatively descriptive by finding detailed information related to the Zakat Community Development program in Kahayya Village, Bulukumba Regency. The results of this study show that several programs have been implemented covering various aspects such as socioeconomic, health, education and religion. In the field of health, disinfectant narrowing, vaccination programs, provision of handwashing, distribution of masks and hand sanitizers to socialization related to the prevention of the spread of the covid-19 virus to the community. Similarly, in the world of education, through ZCD is done the reactivation of reading parks and the development of ICT-based libraries. Socialization in pondok tahfidz as a preventive measure of transmission and healthy life is part of religious empowerment so that students can still learn religion. Especially in the economic aspects formed by several SME communities, namely farmers groups that develop AGROWISATA and horticulture, Kahayya coffee SMEs and honey mustika Kahayya SME groups.Zakat sebagai salah satu pranata dalam Islam, memiliki dimensi spiritual serta mencakup banyak aspek pemberdayaan masyarakat yang meliputi berbagai aspek seperti ekonomi, sosial, kesehatan, pendidikan dan agama, khususnya pada saat terjadi pandemi. Salah satu program pemberdayaan masyarakat oleh lembaga zakat adalah Zakat Community Development. Tujuan penelitian ini untuk mengetahui serta menganalisis konsep pemberdayaan berupa Zakat Community Development pada masa pandemi di Desa Kahayya, Kabupaten Bulukumba. Metode pada penelitian ini adalah kualitatif deskriptif dengan menemukan informasi secara detail terkait program Zakat Community Development di Desa Kahayya, Kabupaten Bulukumba. Hasil penelitian ini menunjukkan bahwa telah dilaksanakan beberapa program yang meliputi berbagai aspek seperti sosial ekonomi, kesehatan, pendidikan maupun keagamaan. Pada bidang kesehatan dilakukan penyemprotan desinfektan, program vaksinasi, penyediaan tempat cuci tangan, pembagian masker dan hand sanitizer hingga sosialisasi terkait pencegahan penyebaran virus covid-19 kepada masyarakat. Demikian pula pada dunia pendidikan, melalui ZCD dilakukan pengaktifan kembali taman baca serta pengembangan perpustakaan berbasis TIK. Sosialisasi di Pondok Tahfidz sebagai langkah pencegahan penularan dan hidup sehat merupakan bagian dari pemberdayaan keagamaan agar santri tetap dapat belajar agama. Terkhusus pada aspek ekonomi yang terbentuk beberapa komunitas UKM yaitu kelompok tani yang mengembangkan AGROWISATA dan holtikultura, UKM Kopi Kahayya serta kelompok UKM Madu Mustika Kahayya.